Taxonomical study of Japanese Aulodrilus Bretscher (Annelida, Clitellata, Tubificinae) with descriptions of two new species - Ohtaka, Akifumi (Zootaxa, 2021)
Seven species of the genus Aulodrilus (Annelida, Clitellata, Tubificinae) are studied, based on new material from Japan. Aulodrilus dentosus sp. nov. is characterized as having tubular atrium, forked or bifid distal ends of dorsal crotchets, but no genital chaetae, and A. aestivus sp. nov. is characterized as having crescent-shaped atrium, median male bursa, and bifid chaetae in the dorsal bundles. Five other congeners are redescribed: A. limnobius Bretscher, A. pluriseta (Piguet), A. pigueti Kowalewski, A. japonicus Yamaguchi, and A. americanus Brinkhurst & Cook. Comparison of taxonomic characters among the 14 species recognized in the genus to date shows that three species differ from other congeners in several features: A. paucichaeta Brinkhurst & Barbour, A. adetus (du Bois-Reymond Marcus), and A. apeniatus Cui & Wang. They are provisionally maintained in the genus.